2021
DOI: 10.1126/sciadv.aba8053
|View full text |Cite
|
Sign up to set email alerts
|

TBC1D3 promotes neural progenitor proliferation by suppressing the histone methyltransferase G9a

Abstract: Genomic changes during human linage evolution contribute to the expansion of the cerebral cortex to allow more advanced thought processes. The hominoid-specific gene TBC1D3 displays robust capacity of promoting the generation and proliferation of neural progenitors (NPs), which are thought to contribute to cortical expansion. However, the underlying mechanisms remain unclear. Here, we found that TBC1D3 interacts with G9a, a euchromatic histone lysine N-methyltransferase, which mediates dimethylation of histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Having established the VOrs, we decided to generate vascularized BOrs by using co-culture strategy. For this purpose, we established the induction system of BOrs from human H9 ESCs according to the methods reported previously ( Lancaster and Knoblich, 2014 ; Mariani et al, 2012 ; Ou et al, 2020 ; Hou et al, 2021 ), with some modifications ( Figure 4—figure supplement 1A ). Cerebral organoids at different developmental stages were stained with neural progenitor markers PAX6 and phospho-vimentin (p-VIM), the proliferation marker KI67, intermediate progenitor marker TBR2, young neuron marker DCX (doublecortin), mature neuron marker TUJ1, and the cortical layer markers (TBR1, CTIP2, SATB2, REELIN), and the results indicated that the BOrs were well induced ( Figure 4—figure supplement 1B–E ).…”
Section: Resultsmentioning
confidence: 99%
“…Having established the VOrs, we decided to generate vascularized BOrs by using co-culture strategy. For this purpose, we established the induction system of BOrs from human H9 ESCs according to the methods reported previously ( Lancaster and Knoblich, 2014 ; Mariani et al, 2012 ; Ou et al, 2020 ; Hou et al, 2021 ), with some modifications ( Figure 4—figure supplement 1A ). Cerebral organoids at different developmental stages were stained with neural progenitor markers PAX6 and phospho-vimentin (p-VIM), the proliferation marker KI67, intermediate progenitor marker TBR2, young neuron marker DCX (doublecortin), mature neuron marker TUJ1, and the cortical layer markers (TBR1, CTIP2, SATB2, REELIN), and the results indicated that the BOrs were well induced ( Figure 4—figure supplement 1B–E ).…”
Section: Resultsmentioning
confidence: 99%
“…Overproliferation of basal radial glial cells (bRGCs) increases cortical surface area and folding in primates (Reillo et al , 2011; Nonaka‐Kinoshita et al , 2013). Recently, some studies have shown that human‐specific genes promote cortical progenitor proliferation and expansion through different mechanisms by inhibiting histone methylation activity or glutaminolysis regulation (Deyama & Duman, 2020; Hou et al , 2021). Increased proliferation capacity of cortical progenitors is critical for cortical expansion.…”
Section: Discussionmentioning
confidence: 99%
“…They have also been shown to recapitulate transcriptomics and the epigenetic landscape of early to mid-fetal development (Luo et al, 2016). Researchers found that inhibition of G9a-mediated H3K9me2 modification in human cerebral organoids resulted in increased NPC proliferation causing organoid expansion, and G9a is likely regulated by the hominoid-specific protein TBC1D3 (Hou et al, 2021). These findings suggest an epigenetic regulatory mechanism for neocortical expansion and possibly ensuing gyrification.…”
Section: Transcriptomics and Omicsmentioning
confidence: 96%